Examining the physical activity levels of academic personnel - Sahin, Ahmet (Progress in Nutrition, 2021)
Study Objectives: In this study, it was aimed to examine the physical activity level of academic personnel according to age and sex variables. Methods: A total of 294 academic personnel (84 female and 210 male) working at Burdur Mehmet Akif Ersoy University participated in the study. International Physical Activity Questionnaire (IPAQ) short form was used to determine the physical activity level of the academic personnel participating in the study. In the analysis of the obtained data, One Way ANOVA, Independent t test, and Chi-Square analyzes were used in the SPSS 22.0 software. Result: It has been determined that the physical activity level of academic personnel was low. When discussed based on demographic variables, it has been determined that the physical activity level of academic personnel showed a statistically significant difference according to age group variable (p<0.05). On the other hand, it was observed that the physical activity level of academic personnel did not show a statistically significant difference according to the sex variable (p>0.05). Conclusion: It can be said that the physical activity level of academic personnel is low and that the physical activity level of academic personnel tends to decrease as age increases.